Self-activated, Nanostructured Composite for Improved CaL-CLC technology - Chen, Jian; Duan, Lunbo; Donat, Felix; Müller, Christoph R.; Anthony, Edward J.; Fan, Maohong (Elsevier, 2018)
The development of bifunctional CaO/CuO matrix composites with both high and stable reactivity is a research priority and key for the development of calcium looping integrated with chemical looping combustion (CaL-CLC), a new CO2 capture technology that eliminates the requirement for pure O2 for the regeneration of CaO-based sorbents. In this work, a simple but effective approach was first used, i.e., solution combustion synthesis (SCS), to produce various nanostructured CaO/CuO matrix composites with homogenous elemental distributions. All CaO/CuO matrix composites possessed increased CO2 uptake in the form of self-activation and excellent cyclically stable O2 carrying capacity over as many as 40 reaction cycles. For instance, the final carbonation conversion of CaO-CuO-1-800-30 was 51.3%, approximately 52.7% higher than that of the original material (33.6%). Here, the self-activation phenomenon have been observed for the first time in contrast to the rapid decay in CO2 uptake capacity previously reported, due mainly to the increase of both specific surface area and pore volume. In-situ X-ray diffraction (in-situ XRD) analysis revealed that no side reactions occurred between CaO/CaCO3 and CuO/Cu during the overall process. All of these results make CaO/CuO matrix composites an attractive candidate for CaL-CLC.
Keywords: Calcium lopping process; Carbon capture; Solution combustion synthesis; Bifunctional composite; In-situ XRD; Self-activation